The Nature of Islamic Ethics and Its Implications for Education - Husni, Husni; Herlina, N. Hani (TAJDID, 2022)
This study seeks to elaborate on the nature of Islamic ethics and its relevance to education. This study is expected to obtain in-depth academic data or information about the nature of Islamic ethics and how it relates to the spirits and values of education. For that purpose, I used the literature review method, which started with identifying, collecting, and grouping relevant articles, to be analyzed and concluded. The results of the study show that the Islamic ethics is relevant to several spirits and values of Islamic education, including sincerity, justice, honesty, feeling the presence of God, obedience to obligations, patience, obedience to the law, forgiveness, commitment to the truth of science, esotericism, and pleasure in giving.